2010
DOI: 10.1136/emj.2009.086538
|View full text |Cite
|
Sign up to set email alerts
|

Is paper-based documentation in an emergency medical service adequate for retrospective scientific analysis? An evaluation of a physician-run service

Abstract: Documentation of vital parameters is carried out incompletely, and documentation of respiratory rate is particularly poor, making calculation of accepted emergency scores infeasible for a significant fraction of a given test population. The suitability of paper-based documentation is therefore limited. Electronic documentation that includes real-time plausibility checks might improve data quality. Further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…Bergrath et al 17 examined paper prehospital records in Germany and found that the documentation compliance of vital parameters ranged from 40.31% to 99.33%. Our own retrospective analysis of paper records at the University of Washington (n=165) found a similar range of compliance: the ‘reason a resuscitation ended’ was recorded only 45% of the time, while the ‘time to first shock’ was recorded 93% of the time 18…”
Section: Introductionmentioning
confidence: 99%
“…Bergrath et al 17 examined paper prehospital records in Germany and found that the documentation compliance of vital parameters ranged from 40.31% to 99.33%. Our own retrospective analysis of paper records at the University of Washington (n=165) found a similar range of compliance: the ‘reason a resuscitation ended’ was recorded only 45% of the time, while the ‘time to first shock’ was recorded 93% of the time 18…”
Section: Introductionmentioning
confidence: 99%
“…Lack of documentation is often highlighted as a limitation for research in emergency medicine, especially for retrospective registry studies [5, 35, 4345]. Putting attention to increase the quality of routinely collected data may enable such data to be an important and effective source to monitor and compare services.…”
Section: Discussionmentioning
confidence: 99%
“…Putting attention to increase the quality of routinely collected data may enable such data to be an important and effective source to monitor and compare services. As such, strategies to increase data capture should be sought [30, 43, 4548]. Training programs may increase data capture, most likely by increasing attention to documentation [43, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of emergency calls, prolonged emergency response times by EMS physicians, and shortages of EMS physicians are having a big impact on the German EMS system. Furthermore, EMS treatment [ 33 , 34 ] and documentation quality [ 35 , 36 ] require urgent improvement.…”
Section: Discussionmentioning
confidence: 99%